2020
DOI: 10.21470/1678-9741-2019-0387
|View full text |Cite
|
Sign up to set email alerts
|

Heparin-coated vs. Non-coated Cardiopulmonary Bypass Circuits: Comparing Immediate Results with Different Target Activated Clotting Time

Abstract: Objective To compare immediate postoperative results in patients receiving heparin-albumin-coated and non-coated circuits. Methods A total of 241 patients undergoing on-pump cardiac surgery were divided into two groups: those receiving heparin-coated circuits (Bioline®, Maquet Cardiopulmonary AG., Hirrlingen, Germany) and those receiving non-coated circuits (Maquet Cardiopulmonary AG., Hirrlingen, Germany). Results Activated clotting times (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…27,28 Hanedan et al showed that shorter activated clotting times could be achieved after CPB using Bioline-coated cannulas and low systemic heparin dosage compared to uncoated cannulas; however, the intensive care unit (ICU) length of stay and in-hospital mortality rate were similar in both cases. 29 The Trillium Biosurface, another type of coating, consists of two layers: an underlayer of hydrophilic polymer that can bind tightly to the surface of most materials and act as a primer; the top layer that is a covalently bonded polymer of heparin that contains sulphate or sulphonate groups and polyethylene oxide chains that act as anticoagulants. 28,30 Palanzo et al showed that the Trillium Biosurface was not significantly different from the Carmeda coating when comparing several metrics, such as the post-CPB platelet count and postoperative receipt of platelet infusions.…”
Section: Heparin-contained Coatings For Commercial Usementioning
confidence: 99%
“…27,28 Hanedan et al showed that shorter activated clotting times could be achieved after CPB using Bioline-coated cannulas and low systemic heparin dosage compared to uncoated cannulas; however, the intensive care unit (ICU) length of stay and in-hospital mortality rate were similar in both cases. 29 The Trillium Biosurface, another type of coating, consists of two layers: an underlayer of hydrophilic polymer that can bind tightly to the surface of most materials and act as a primer; the top layer that is a covalently bonded polymer of heparin that contains sulphate or sulphonate groups and polyethylene oxide chains that act as anticoagulants. 28,30 Palanzo et al showed that the Trillium Biosurface was not significantly different from the Carmeda coating when comparing several metrics, such as the post-CPB platelet count and postoperative receipt of platelet infusions.…”
Section: Heparin-contained Coatings For Commercial Usementioning
confidence: 99%
“…Recent advances in bypass technologies have created biocompatible surfaces to potentially decrease platelet activation during CPB, therefore, reducing the number of complications after surgery. Heparin-coated circuits are widely used because they seem not to cause excessive platelet activation as compared to non-coated circuits [ 5 ]. Another commonly used circuit poly-2-methoxyethyl acrylate (PMEA) has a protective water layer that allows proteins to retain their conformation and reduce adherence to foreign surfaces [ 6 ].…”
Section: Introductionmentioning
confidence: 99%